Unifying Psychology: Shared Ontology and the Continuum of Practical Assumptions. Issue 1 (March 2014) - Marsh, Tim; Boag, Simon
Critics have described psychology as a science impaired by disunity. The most recent special issue of Review of General Psychology sought to specifically address this concern, seeking perspectives from a wide range of theorists, each of whom offered their tradition's approach to how psychology as a whole may be integrated into a more unified whole. To continue this discussion, this article draws upon examples from the special issue, the disunity crisis literature, and wider writings in the philosophy of science, to explore the theoretical and conceptual divisions that foster ambiguity, confusion, and apparent irreconcilable differences between the disparate fields of psychology. The authors conclude that the majority of contemporary, scientific psychology is oriented toward a shared physical ontology, which can serve as a common grounding point from which the conceptual and theoretical differences of disparate fields may be meaningfully framed and evaluated. To this end, this article proposes that the various research traditions of psychology can be understood through their positions along a continuum of practical assumptions, which embodies the inherent conflict between two scientific priorities: metaphysical certainty (the safe end of the continuum) and practical experimental predictions (the risky end of the continuum). Three theoretical perspectives offered in the unification special issue are examined under this framework: situational realism (a distinctly safe approach), developmental evolutionary psychology (an intermediate approach), and the Tree of Knowledge unified theory (a relatively risky approach). The authors explore how the recommendations of each approach can be seen as a function of its position on the continuum of practical assumptions, and the implications of this understanding for future integrative efforts is discussed.